Learning to change the world - Larike H. Bronkhorst; Marlon Renes; Dagmar Bon; Noah S. Rookmaaker; Anne van Leest (EARLI, 2024)
Feeling the urgency of the climate crisis and judging current societal (re)action insufficient, young adults increasingly engage in climate activism. While individual learning is not the objective of climate activism, research has documented that young adults learn in climate activism movements. This study traces young adults' learning across climate activism and different life-wide contexts, explicating dis/continuities in learning. Content-analysis of interviews with twelve self-defined climate activists indicates that in and across climate activism and other life-contexts young adults report a) learning about the climate, activism, intersectionality, democracy and system structures, b) learning to organize, socialize and take perspective(s), while c) progressively expressing who and how they want to be(come). Young adults described experiencing discontinuities between the context of their climate activism and other contexts such as education, friends and family, and their efforts to re-establish continuities are an important part of their learning. When young adults experience discontinuity across contexts structurally, they keep their climate activism to themselves and/or disengage from education, among others. Making space in education more explicitly for sharing and shaping what matters to youth seems desirable.